Heart rate turbulence assessment in systemic sclerosis: the role for the detection of cardiac autonomic nervous system dysfunction - Bienias, Piotr; Ciurzyński, Michał; Glińska-Wielochowska, Maria; Szewczyk, Agnieszka; Korczak, Dariusz; Kalińska-Bienias, Agnieszka; Gliński, Wiesław; Pruszczyk, Piotr (Rheumatology (Oxford, England), 2010)
Objective. To assess the heart rate turbulence (HRT) in patients with SSc as a method of assessment for cardiac autonomic nervous function. Methods. We prospectively studied 68 consecutive patients with SSc before inclusion in the study. After a detailed clinical evaluation, including echocardiography, 45 subjects [aged 54.6 (14.7) years; 40 women] underwent 24-h Holter monitoring for HRT and time- and frequency-domain heart rate variability (HRV) assessment. Results were compared with those in 30 age- and sex-matched healthy controls. Results. As compared with controls, HRT was impaired in SSc patients: the median turbulence onset (TO) was higher (P = 0.0001) and the median turbulence slope (TS) was lower (P = 0.0003). Abnormal HRT (TO ⩾0.0% and/or TS ⩽2.5 ms/RR) was found in 42% of SSc patients. Moreover, SSc duration correlated negatively with values of TS (r = −0.3; P = 0.045). HRT did not differ between diffuse and limited SSc groups. All estimated time- and the majority of frequency-domain values of HRV parameters in SSc were significantly lower than in controls. Significant correlations were also demonstrated between HRT and HRV parameters. Conclusions. HRT, like HRV assessment, indicates a frequent impairment of the cardiac autonomic nervous system in SSc patients, irrespective of the SSc type.